2011
DOI: 10.1177/1947601911408077
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Neuronal Function by Ras-GRF Exchange Factors

Abstract: Ras-GRF1 (GRF1) and Ras-GRF2 (GRF2) constitute a family of guanine nucleotide exchange factors (GEFs). The main isoforms, p140-GRF1 and p135-GRF2, have 2 GEF domains that give them the capacity to activate both Ras and Rac GTPases in response to signals from a variety of neurotransmitter receptors. GRF1 and GRF2 proteins are found predominantly in adult neurons of the central nervous system, although they can also be detected in a limited number of other tissues. p140-GRF1 and p135-GRF2 contain calcium/calmodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
64
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 111 publications
0
64
0
Order By: Relevance
“…The function of RASGRF1 in normal stomach and during gastric tumorigenesis is largely unknown, but it may exert oncogenic effects through activation of Ras proteins (35). On the other hand, one recent study showed that RASGRF proteins bind directly to Cdc42, another Ras-related GTPbinding protein, and suppress Cdc42-mediated cellular processes, including tumor cell invasion and transformation (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The function of RASGRF1 in normal stomach and during gastric tumorigenesis is largely unknown, but it may exert oncogenic effects through activation of Ras proteins (35). On the other hand, one recent study showed that RASGRF proteins bind directly to Cdc42, another Ras-related GTPbinding protein, and suppress Cdc42-mediated cellular processes, including tumor cell invasion and transformation (38).…”
Section: Discussionmentioning
confidence: 99%
“…RASGRF1 and RASGRF2 constitute a gene family encoding guanine nucleotide exchange factors (GEF), which activate Ras GTPase by promoting the release of bound GDP, enabling activating GTP to take its place (35). RASGRF proteins are predominantly expressed in adult neurons in the central nervous system, and are involved in a wide range of neuronal functions.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, pharmacological block of p38 in hippocampal area CA1 impairs extinction of inhibitory avoidance memory (Rossato et al 2006). p38 activation by Ras-GRF1 has been implicated in the induction of long-term depression (LTD) (for review, see Feig 2011). Finally, JNKs also become activated during hippocampal memory formation.…”
Section: Mapk Familymentioning
confidence: 99%
“…3). In the case of Ras activation of the ERK cascade, the calcium/ calmodulin-sensitive guanine nucleotide exchange factors Ras-GRF1 and Ras-GRF2 are important (Feig 2011). The ERK1/2-MSK1 pathway requires cAMP production by calcium/calmodulin-dependent adenylate cyclases (Sindreu et al 2007;Xia and Storm 2012; also see Ahi et al 2004).…”
Section: Mapk Familymentioning
confidence: 99%
“…The Cdc25 homology domain at the C terminus catalyzes exchange of GDP to GTP on Ras family proteins, whereas the Dbl homology-pleckstrin homology domain functions as a GEF for Rac proteins (4). RasGRF2 was initially identified in neuronal tissues, and its known functions in the nervous system include regulation of NMDA receptor signaling and synaptic plasticity (5). Although mechanisms underlying the restricted tissue distribution of RasGRF2 are not fully understood, recent studies have suggested that RasGRF2 expression is suppressed in different human cancers, implying a tumor suppressive role (4), but by as yet unclear mechanisms.…”
mentioning
confidence: 99%